Epidemiology of multimorbidity in childhood cancer survivors: a matched cohort study of inpatient hospitalisations in Western Australia - Tasnim Abdalla; Jeneva L. Ohan; Angela Ives; Daniel White; Catherine S. Choong; Max Bulsara; Jason D. Pole (BJC Reports)
Abstract Background Childhood cancer survivors (CCS) experience an elevated burden of health complications, underscoring the importance of understanding the patterns of multimorbidity to guide the management of survivors with complex medical needs. Methods We examined the patterns of hospitalisations with multimorbidity in 5-year CCS (n = 2938) and age- and sex-matched non-cancer comparisons (n = 24,792) using statewide records of inpatient admissions in Western Australia from 1987 to 2019. Results Multimorbidity rates were higher for CCS (10.6, 95%CI 10.2–10.9) than for non-cancer comparisons (3.2, 95%CI 3.2–3.3). CCS exhibited a significantly higher adjusted hazard ratio of multimorbidity, particularly when admitted for neoplasms (14.6, 95%CI 11.2–19.1), as well as blood (7.3, 95%CI 4.9–10.7), neurological and sensory (5.2, 95%CI 4.2–6.6), and cardiovascular (3.6, 95%CI 2.6–4.8) diseases. By the age of 55 years, chronic multimorbidity was more prevalent in survivors than in comparisons (14.5% vs. 5.3%). Psychiatric disorders were common comorbidities, particularly in those admitted for neurological and sensory (71.1%), endocrine (61.5%), and digestive (59.3%) diseases. Multimorbidity during hospitalisation increased the length of hospital stay (p < 0.05). Key condition clusters included (1) psychoactive substance  dependence, alcohol misuse, and other mental disorders; (2) hypertension, diabetes, kidney disease, and musculoskeletal diseases; (3) epilepsy, hypothyroidism, and other liver diseases; and (4) hypertension, kidney disease, and other liver diseases. Conclusions These findings suggest that exposure to cancer in childhood elevates the risk of multimorbidity. The reconfiguration of healthcare delivery to enhance personalised care and clinical integration is essential for effectively managing multimorbidity in this population.